Methodology For Forming Creative Imagination Of Primary School Students Through Design Technologies - Sanakulov Khamrakul Rizakulovich (Periodica Journal, 2025)
This article will cover the methodology for shaping the creative imagination of students of a small school age through design technologies. Through the use of Design Thinking (design thinking) steps, the study is based on the methodology of forming students ' skills to identify a problem, create an idea, prototype development and provide a creative solution. This methodology serves to develop technological competencies in students, engage in creative activities and support independent creative research
Keywords: Junior school age students; creative imagination; design technologies